(untitled) (Zdravstveni glasnik, 2024)
Introduction: Due to the consequences of the COVID-19 pandemic, experts have expressed concern for psychological functioning and well-being globally, with a particular reference to life quality disorder. Aim: To determine the connectin of recovery and the degree of life quality. Respondents and methods: A cross-sectional survey is carried out. The sample in the research consist of persons of both sexes at the age of 18, who have recovered from the infection, reviewing more than a year since the beginning of this research. The test survey was done by 384 respondents, which was carried out from October to December 2022. It was used a questionare survey, designed for research purpose, consisting of socio-demographich characteristics, characteristics of COVID-19 infection and consequences of COVID19 infection. Results: By the comparison of established frequencies of response, confirmations of agreement and disagreement of the claims examinated is established that significantly higher percentage of respondents have noticed, in their functioning after COVID-19 infection, the appearance of fatigue and muscles weakness (65,9%), significant hair loss (57,8) and higher level of symptoms of depression and anxiety (43,8%). Conclusion: The COVID-19 pandemic has markedly influenced life quality and has affected all aspects of life and health.